2006
DOI: 10.1111/j.1574-6968.2005.00048.x
|View full text |Cite
|
Sign up to set email alerts
|

A new species ofPythiumwith ornamented oogonia: morphology, taxonomy, internal transcribed spacer region of its ribosomal RNA, and its comparison with related species

Abstract: Pythium spiculum sp. nov. was isolated from soil samples taken in a vineyard in the Burgundian region of France and from different locations in Spain and Portugal. The oomycete has spiny oogonia and does not sporulate readily. It resembles Pythium mamillatum Meurs, but has its own distinguishing characteristics. It also exhibits sickle-shaped as well as spherical appressoria which at times are associated with sex organs like those found in Pythium abappressorium Paulitz and Pythium contiguanum Paul. Sequencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 20 publications
1
21
0
1
Order By: Relevance
“…attrantheridium) to indicate relatedness to the closest named species match. The identity of each species was confirmed by evaluating up to 10 isolates for morphological characteristics according to the taxonomic keys of van der Plaats-Niterink (41) and Waterhouse (42), or to the original species descriptions (22,34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…attrantheridium) to indicate relatedness to the closest named species match. The identity of each species was confirmed by evaluating up to 10 isolates for morphological characteristics according to the taxonomic keys of van der Plaats-Niterink (41) and Waterhouse (42), or to the original species descriptions (22,34).…”
Section: Methodsmentioning
confidence: 99%
“…ITS sequences were compared to sequences available in GenBank using BLAST to identify each isolate to species. Sequences from ex-type cultures or authentic strains as described by van der Plaats-Niterink (41) and Levesque and de Cock (24), including those reported as new or potentially new species (22,34), were used in analyses when available. Sequences with less than 99% identity to ex-type cultures and authentic strains could be considered as variants of the most closely matched species, or as putative new species.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After checking the roots of wilted and JA-treated opr7-5 opr8-2 plants, we found that the former were necrotic and the latter were healthy (Figures 7D and 7E). Numerous oospores were observed in the necrotic roots ( Figure 7D) and, following isolation and purification, were later identified as Pythium aristosporum by cloning and sequencing the internal transcribed spacer (ITS) region of nuclear rRNA genes using primers ITS1 and ITS4 (Paul et al, 2006) and also by characteristics of the oospores and antheridia. The isolates from the necrotic roots of diseased opr7 opr8 plants in the field were also identified as P. aristosporum.…”
Section: Ja Is a Positive Regulator Of Anthocyanin Pigmentation In Mamentioning
confidence: 99%
“…Quite a number of the members of the genus Pythium are known for their ornamented oogonia (female gametangia), and of these members the most commonly found is Pythium echinulatum. Since then, the present author has added four more: Pythium ornamentatum, Pythium radiosum, Pythium ornacarpum and Pythium spiculum (Paul, 1987(Paul, , 1992(Paul, , 1999Paul et al, 2006). Plaats-Niterink (1981) recognized 21 species of Pythium having ornamented oogonia.…”
Section: Introductionmentioning
confidence: 99%